(untitled) (Management Dynamics, 2024)
An empirical study was conducted with the objective of identifying the elements that have an impact on the level of satisfying experience by customers at the Kalimati fruit and vegetable market in Nepal. This study employed the explanatory research design with a quantitative approach using a structured questionnaire. Data were collected from the customers of the Kalimati vegetable market through the use of convenience sample techniques. A structural equation model was utilized in order to do the analysis on the data. About consumer happiness, one of our findings demonstrates that the quality of the product, the price of the product, the availability of the product, and the quality of the service all have a substantial influence; the sense of security has no impact at all. The majority of the existing literature supports the idea that quantity and pricing are factors that have an effect on customer satisfaction. This study significantly contributes to both academic and practical research. To meet consumer needs in the vegetable market, partnerships focused on fair pricing and product quality are essential. The findings underscore a complex, interdependent relationship among components, influenced by factors such as the industry sector, product type, and sample characteristics. Joint effect analysis using SEM of product price, product quality, product availability, and product security on customer satisfaction with vegetables.